2018
DOI: 10.1186/s12886-018-0946-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of complex Descemet Stripping Endothelial Keratoplasty performed by cornea fellows

Abstract: BackgroundA major obstacle that academic institutions face is the steep learning curve for cornea fellows initially learning to perform Descemet Stripping Endothelial Keratoplasty (DSEK). The purpose of this study is to evaluate the outcomes of complex DSEK performed by cornea fellow supervised by an attending surgeon at an academic institution.MethodsPatients who underwent a complex DSEK procedure performed by a cornea fellow during the years 2009-2013 were included. All the surgeries were supervised by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…However, there were no signi cant statistical differences between the occurrence of this complication in nDSEK and DSEK eyes. The rate of acute high intraocular pressure was relatively lower, as compared to the 10.5% reported in the study conducted by Daubert et al [17] but higher than 2.8% reported by study of Basaket al [20]. The higher rate of acute high intraocular pressure in our present study could be associated with the use of a full intracameral air tamponade to obtain rm attachment of the donor at the end of surgery without releasing the air postoperatively.…”
Section: Complicationscontrasting
confidence: 60%
See 2 more Smart Citations
“…However, there were no signi cant statistical differences between the occurrence of this complication in nDSEK and DSEK eyes. The rate of acute high intraocular pressure was relatively lower, as compared to the 10.5% reported in the study conducted by Daubert et al [17] but higher than 2.8% reported by study of Basaket al [20]. The higher rate of acute high intraocular pressure in our present study could be associated with the use of a full intracameral air tamponade to obtain rm attachment of the donor at the end of surgery without releasing the air postoperatively.…”
Section: Complicationscontrasting
confidence: 60%
“…First, eye conditions such as prior cataract-vitreous-retinal surgery (ocular trauma history ), glaucoma drainage implantation, complicated eye with severe corneal edema, abnormal anterior segment such as anterior synechia, aphakia, and iris defect, can make endothelial keratoplasty more challenging for these complex cases. Second, factors related to the surgery itself, such as incision size, donor tissue preparation, as well as graft delivery devices, rebubbling for donor tissue dislocation and the learning curve of EK for the surgeon [14,15,16,17] also associated with postoperative corneal endothelial loss. All of these factors can affect the ECL and lead to higher ECL as observed in our present study.…”
Section: Endothelial Cell Density and Endothelial Cell Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other authors have shown that donor dislocation is the most common complication seen in DSEK and with experience and time, the dislocation rate is reduced. [ 19 , 20 ] Cystoid macular edema and retinal detachment were not seen in any of the postoperative cases.…”
Section: Discussionmentioning
confidence: 88%